Hemolysis : an unresolved dispute in laboratory medicine - Lippi, Giuseppe (De Gruyter, 2012)
Defined as red blood cell break down and the release of hemoglobin and intracellular contents into the plasma, hemolysis can seriously impact patient care as well as the laboratory's reputation through its affect on test results. Therefore, the European Preanalytical Scientific Committee, in collaboration with the International Federation of Clinical Chemistry Working Group on Patient Safety, have designed a questionnaire to collect data on prevalence and management of hemolytic specimens referred to the clinical laboratories for clinical chemistry testing. This book will help identify the areas where hemolysis occurs most frequently, which can, in turn, guide further analysis about why it is occurring. Once these elements are known, practices and procedures can be implemented to dramatically reduce hemolysis and avoid erroneous laboratory results affecting patient care and increasing laboratory costs.
Keywords: Hematology -- Standards.; Blood -- Examination.; Hemolysis and hemolysins.; Hematologic Tests -- standards; Hemolysis; Blood Specimen Collection -- standards; Blood Specimen Collection; Hématologie -- Normes.; Sang -- Examen.; Hémolyse.; MEDICAL -- Hematology.; Hemolysis and hemolysins; Blood -- Examination; Hematology -- Standards